Successful Use of Ectopic Pelvic Kidney for Living Related Donation Technical Aspects and Literature Review - R. C. Minnee; H. J. A. N. Kimenai; J. van de Wetering; J. N. M. Ijzermans (Case Reports in Transplantation)
Ectopic pelvic kidneys can provide an additional source of organs for transplantation. They are often excluded from donation in living donation programs mainly due to aberrant vascular and urinary anatomies. We present a donor with an ectopic left kidney, who successfully donated his kidney. The use of ectopic pelvic kidney for living kidney transplantation is a highly demanding surgical procedure but after extensive preoperative investigation in high volume centers with surgical expertise in vascular reconstruction and access surgery, ectopic pelvic kidneys should not be a contraindication for donation and should be considered as a viable option.